Viśvavallabha-vr̥kṣāyurvedaḥ : Dakārgalavijñānataruropaṇaṃcikitsāvidhauca : Hindīvyākhyopetam - Cakrapāṇi Miśra (Nyū Bhāratīya Buka Kôrapareśana, 2005)
Treatise on techniques of growing plants and trees with astrological aspects of Ayurvedic medicinal plants; includes Vr̥kṣāyurveda and Dakārgala chapters from Br̥hatsaṃhitā of Varāhamihira, 505-587.